The European/International Fibromuscular Dysplasia Registry and Initiative (FEIRI)—clinical phenotypes and their predictors based on a cohort of 1000 patients. Issue 3 (13th April 2020) - Pappaccogli, Marco; Di Monaco, Silvia; Warchoł-Celińska, Ewa; Lorthioir, Aurélien; Amar, Laurence; Aparicio, Lucas S; Beauloye, Christophe; Bruno, Rosa Maria; Chenu, Patrick; de Leeuw, Peter; De Backer, Tine; Delmotte, Philippe; et al.
Abstract: Aims: Since December 2015, the European/International Fibromuscular Dysplasia (FMD) Registry enrolled 1022 patients from 22 countries. We present their characteristics according to disease subtype, age and gender, as well as predictors of widespread disease, aneurysms and dissections. Methods and results: All patients diagnosed with FMD (string-of-beads or focal stenosis in at least one vascular bed) based on computed tomography angiography, magnetic resonance angiography, and/or catheter-based angiography were eligible. Patients were predominantly women (82%) and Caucasians (88%). Age at diagnosis was 46 ± 16 years (12% ≥65 years old), 86% were hypertensive, 72% had multifocal, and 57% multivessel FMD. Compared to patients with multifocal FMD, patients with focal FMD were younger, more often men, had less often multivessel FMD but more revascularizations. Compared to women with FMD, men were younger, had more often focal FMD and arterial dissections. Compared to younger patients with FMD, patients ≥65 years old had more often multifocal FMD, lower estimated glomerular filtration rate and more atherosclerotic lesions. Independent predictors of multivessel FMD were age at FMD diagnosis, stroke, multifocal subtype, presence of aneurysm or dissection, and family history of FMD. Predictors of aneurysms were multivessel and multifocal FMD. Predictors of dissections were age at FMD diagnosis, male gender, stroke, and multivessel FMD. Conclusions: The European/International FMD Registry allowed large-scale characterization of distinct profiles of patients with FMD and, more importantly, identification of a unique set of independent predictors of widespread disease, aneurysms and dissections, paving the way for targeted screening, management, and follow-up of FMD.